SOSIALISASI DAN PENDAMINGAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA UNTUK MENINGKATKAN PENDAPATAN PELAKU UMKM DI DESA BERCAK, KECAMATAN WONOSAMUDRO, KABUPATEN BOYOLALI - BENI PRABOWO; ALEAN KISTIANI H.S; DONNA SETIAWATI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
This Community Service Program ( KKN ) was held in Bercak Village, Wonosamodro District, Boyolali Regency, with the aim of equipping students with the ability to approach the community and form attitudes and behavior to always be sensitive to problems faced by the community. Empowering the community through various aspects of development as an effort to achieve prosperity. The potential of spotting villages is the number of umkm actors in the village, so the authors hold a main work program